The Impact of Training Program to Develop the Most of Functional and Skill Abilities for the Players in the Volleyball - Maysaloun Zuhair Hussein (Journal of Global Pharma Technology, 2016)
The preparation stage in the quality of the year and the private is the basis on which the team is built and which depends on access to high levels of sports, both in terms of functional or technical and the requirements of training in volleyball is many and multiple, the training process has become complex, and requires planning based on the sound scientific foundations through which possible to achieve the best possible results in light of the capabilities of the player and its potential, so that training these capabilities is the cornerstone on which the training is based on the type of the game as the player cannot reach the high performance without the availability of such Capacity and sustain training and improve their level, and the importance of this study in building the basic rule of volleyball and the need to develop a training curriculum interested in how to train the early stages of the year, which prompted the researcher to engage in this research attempt to apply the scientific foundations in the training of volleyball with appropriate ages and important in sports training.The research objectives to:Preparation of a training curriculum to develop some of the skills and skills of the players of the volleyball.Knowledge of the impact of the curriculum in developing some of the functional and skill capabilities of the players of the volleyball.The researchers used the experimental method (designing two groups) to suit the problem of research. The research community determined the club members in front of Al-Mutaqin and Al-Husseiniya club in the youth category. The number of players was 32 and a simple random sample of 24 players was selected and divided into two groups (Experimental and control).From the results obtained, the researchers reached the following conclusions:The training curriculum has a positive effect on the development of functional abilities (lactic non-oxygen ability, lactic oxygenation, oxygen capacity), and skill capabilities (Service, defense of service, preparation (passing), spike and block).The evolution of experimental group members was better with the functional and skillful abilities of all tests compared to control group members.The highest significant value of the experimental group in the non-lactic capacity tests for the functional abilities and the overwhelming impact on the skill capacity.Keywords: Training program, Functional and skill abilities.